Inhibition of SLPI ameliorates disease activity in experimental autoimmune encephalomyelitis - Müller André (BMC Neuroscience, 2012)
Abstract Background The secretory leukocyte protease inhibitor (SLPI) exerts wide ranging effects on inflammatory pathways and is upregulated in EAE but the biological role of SLPI in EAE, an animal model of multiple sclerosis is unknown Methods To investigate the pathophysiological effects of SLPI within EAE, we induced SLPI-neutralizing antibodies in mice and rats to determine the clinical severity of the disease. In addition we studied the effects of SLPI on the anti-inflammatory cytokine TGF-β. Results The induction of SLPI neutralizing antibodies resulted in a milder disease course in mouse and rat EAE. SLPI neutralization was associated with increased serum levels of TGF-β and increased numbers of FoxP3+ CD4+ T cells in lymph nodes. In vitro, the addition of SLPI significantly decreased the number of functional FoxP3+ CD25hi CD4+ regulatory T cells in cultures of naive human CD4+ T cells. Adding recombinant TGF-β to SLPI-treated human T cell cultures neutralized SLPI's inhibitory effect on regulatory T cell differentiation. Conclusion In EAE, SLPI exerts potent pro-inflammatory actions by modulation of T-cell activity and its neutralization may be beneficial for the disease.